Pemanfaatan Media Pembelajaran Vidio Tutorial Terhadap Hasil Belajar Siswa Kelas X di SMKN 1 Dua Koto - Putri, Rizka; Darmawati, Gusnita; Rahayu, Della Sri (Yayasan Lembaga Studi Makwa, 2024)
This study discusses the use of video tutorial learning media on learning outcomes in class X at SMKN 1 Dua koto, Pasaman Regency. With this media to improve the learning outcomes of class X students at SMKN 1 Dua Koto. This video tutorial is a form of implementing information technology developments at SMKN 1 Duakoto. Along with the development of information technology, many media have developed. Media is an intermediary or source of information or messages and there is a recipient of messages or information. This study aims to determine the pen use of video tutorials on the learning outcomes of class X students at SMKN 1 Dua Koto. This study uses a type of experimental quantitative research by purchasing samples by comparing the control class and the experimental class. The data analysis technique used is the normality test, homogeneity test, and the hypothesis testing stage.